Thwarting the Blight: A Comprehensive Review of Traditional and Molecular Germplasm Screening Techniques for Black Spot Resistance in Roses (Journal of Agriculture and Biology, 2024)
Diplocarpon rosae causing rose black spot disease, is one of the most devastating pathogens, that affect the quality of roses, and is responsible for huge yield losses, worldwide. Many approaches have been applied to control this disease including developing resistance variety. However, this review widely evaluates different screening germplasm methods to control the black-spot disease in rose. Additionally, in this review, many major issues influencing the black-spot disease resistance, including environmental factors, plant-pathogen interaction and genetic diversity, providing a complete thoughtful of the multifaceted nature of this disease. Moreover, the variety of screening technique ranging from conventional field assessment to contemporary molecular approaches, emphasizing their respective benefits and restrictions. But, the finding and employing new resistance genes is very difficult due to highly genetic diversity of this pathogen, especially, when their interaction of this pathogen to plant are not completely understood. Because, various isolates and strains of pathogen can relate in diverse ways with different germplasm, making it challenging to identify uniform resistance among all strains. Furthermore, many environmental factors including light, temperature and humidity support to increase the disease development, leading reduce the resistance and tolerance of plant against pathogen. Whereas, developing resistance germplasm might be helpful to control this disease and reduce pathogen infection in plants. In this regard, many plant-omics studies such as transcriptome, genome re-sequencing and proteomics have been widely studied to find out candidate resistance (R) protein and genes, which related to the black-spot disease. This review seeks to provide researchers as well as growers and breeders with a through recourse that combine recent information on the assessment of rose germplasm against black spot disease resistance. By employing newly approaches, we aimed to accelerate the growth of rose varieties, that are beautifully attractive and strong in the appearance on this determined blight. In the last, our collective finding to addresses the issues could be increase the sustainability and visual attractiveness of rose cultivation for future generations.